Association of MTHFR polymorphism, folic acid and vitamin B12 with serum homocysteine levels in pregnant women - Ana Bošković; Ana Ćuk; Vedrana Mandrapa; Ana Dugandžić Šimić; Ivona Cvetković; Martina Orlović Vlaho; Tanja Krešić; Tanja Tomić; Vajdana Tomić (Biomolecules & Biomedicine, 2024)
Homocysteine is known to be associated with adverse vascular and metabolic effects, as well as pregnancy complications. Its serum levels are influenced by the function of the enzyme methylenetetrahydrofolate reductase (MTHFR) and the dietary intake of folic acid, vitamin B12, and methionine. In this cross-sectional study, we investigated the association of genetic polymorphisms of the MTHFR gene with vitamin status in pregnant women during mandatory folic acid supplementation. The study included 102 pregnant women between 24 and 28 weeks of gestation who were attending regular outpatient examinations at the maternity clinic. Homocysteine, folic acid, vitamin B12 levels, and MTHFR gene polymorphisms (C677T and A1298C) were analyzed. Significant associations were found between vitamin B12 and folic acid levels with homocysteine (P < 0.001), with lower serum levels of these vitamins being associated with higher homocysteine levels. Surprisingly, there was no significant association between MTHFR genetic polymorphisms and serum homocysteine levels, likely attributed to the supplementation of folic acid and vitamin B12 in vitamin supplements for pregnant women, which counteracts the effect of the mutation. Remarkably, a high prevalence of MTHFR gene mutations was found, with the C677T polymorphism present in 56.9% and the A1298C polymorphism in 87.2% of pregnant women. These findings emphasize the importance of adequate folic acid and vitamin B12 intake during pregnancy to regulate homocysteine levels. Although the MTHFR gene mutations were highly prevalent, their influence on homocysteine levels in this population appears to be mitigated by vitamin supplementation. Further research is warranted to explore the impact of these mutations on other aspects of pregnancy outcomes. The trial is registrated at Clinicaltrail.gov (NCT04952324).